Development of C3‐Symmetric Tris‐Urea Low‐Molecular‐Weight Gelators. Issue 2 (25th February 2016) - Yamanaka, Masamichi
Abstract: This article describes recent developments in C 3 ‐symmetric tris‐urea low‐molecular‐weight gelators and their applications. The C 3 ‐symmetric tris‐ureas are excellent frameworks to form supramolecular polymers through noncovalent interactions. In organic solvents, hydrophobic tris‐ureas form supramolecular gels. Amphiphilic tris‐ureas form supramolecular gels in aqueous media. Functional supramolecular gels were prepared by introducing appropriate functional groups into the outer sphere of tris‐ureas. Supramolecular hydrogels obtained from amphiphilic tris‐ureas were used in the electrophoresis of proteins. These electrophoreses results showed several unique characteristics compared to typical electrophoreses results obtained using polyacrylamide matrices. Abstract : Coming together as one : Diverse supramolecular gels of organic solvents and aqueous solutions are developed from structurally related C 3 ‐symmetric tris‐urea frameworks. Supramolecular hydrogels obtained from amphiphilic tris‐ureas can be used in the electrophoresis of proteins.